Reconceiving Extraterritorial Jurisdiction From Formality to Function - Li, Kevin (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2022)
Despite the century-long reiteration of the principle of territorial sovereignty, States are increasingly resorting to extraterritorial jurisdiction. This book comparatively analyses this phenomenon in US and European practice in the areas of economic sanctions, export control, anti-corruption and business & human rights. It makes the case that the territoriality-based system of jurisdiction is inadequate for allocating regulatory competences between States in international practice. As a result, this book proposes a new approach to conceptualizing jurisdiction by moving away from formal territoriality and towards considering extraterritorial jurisdiction from its function as an exercise of public authority.